KEBERADAAN REKAMAN CLOSED CIRCUIT TELEVISION (CCTV) DALAM PEMBUKTIAN PADA SISTEM PERADILAN PIDANA INDONESIA - Untung Regama (Magister Ilmu Hukum, Universitas Wisnuwardhana Malang, 2019)
The use of CCTV (Television Closed Circuit Television) evidence as evidence still causes claims. Some are automatically used as evidence, and some are not in court proceedings. This research aims to find why CCTV equipment can be used as evidence and evidence used for CCTV equipment. The type of research used by the author is that this study will be prepared using a type of normative juridical research. The research method uses the statutory approach. Secondary legal materials examine secondary primary legal materials in the form of literature studies (literature, research results, scientific magazines, scientific bulletins, scientific journals.) concerning legal understanding, legal norms, legal theories, and doctrines related to the topic in question. The results of this study are normative authors who issued a second view recording CCTV as an electronic evidence device that won evidence in the Criminal Procedure Code. As proof, CCTV is strong and has a value of proof, must meet the provisions that are guaranteed originality and authenticity, have relevance to the subject matter, and the relevance of the relationship with one contribution to another evidence. These provisions must be with the procedures and regulations that have been determined by applicable legislation. Implementation of evidence in CCTV cameras is still experiencing problems, namely legal and non-legal constraints. Keywords: CCTV, Proof, Judiciary Criminal